NUEVOS REGISTROS DE HELECHOS Y CONÍFERAS DEL CRETÁCICO INFERIOR EN LA CUENCA DEL VALLE SUPERIOR DEL MAGDALENA, COLOMBIA (2016)
Descriptions of new plant macrofossils from the Lower Cretaceous (Aptian-Albian) of Colombia are presented. The studied material was collected in the Upper Magdalena Valley Basin in three exposing levels from the Yaví and Caballos formations. The fossil remains are associated to filicopsids and conifers. Within the ferns, the family Marsileaceae, constitutes an important group identified in the fossil flora because it is proposed as the first record of aquatic ferns for the Lower Cretaceous of Colombia. Additionally, abundant sterile bipinnate fronds with lanceolate pinnule and pecopteridea venation remains were included in the morphogenus Cladophlebis sp. The studied conifers presented vegetative structures associated to reproductive organs. The most abundant sterile fragments were included within the morphogenus Brachyphyllum sp. and ovuliferous scales of Araucarites sp. (Araucariaceae) type. Together these new findings represent a key aspect to understand the biogeography of the mentioned groups and, simultaneously, contribute to the knowledge of the Cretaceous plant fossils from Colombia.